Efecto de la edad sobre la población de folículos pilosos y su relación con características de mohair en caprinos de Angora - Carro, N.D. (2010)
The Angora goats are bred in the north Patagonia signifi cantly contributing to the economy of wide sectors of the rural population. Mohair quality, represented partially by staple length and mean fibre diameter, is strongly related to follicle density and proportion of active skin follicles, strongly influenced by age. The aim of this work was to determine the follicular population evolution and its relationship with mohair quality traits. Animals of five age groups were selected; and skin and fiber samples were taken. Follicle density diminished significantly from 53 months; secondary to primary follicle ratio reached a minimum value at 41 months; follicle internal diameter increased significantly until 53 months, then decreasing; percentage of active secondary follicles showed a significant decrease until 65 months, whereas no differences were recorded for primary follicles. Significant correlations between follicular characteristics and fleece characteristics were found.